Mucuna pruriens restores spermatogenesis in mice after exposure to 2-methoxyethanol - Putu Oky Tania; Sri Winarni (Universa Medicina, 2013)
Background Increasing industrial activity is causing many problems in reproductive health, such as infertility. The factors causing infertility are hormones, infection, radiation, drugs and chemicals. One of these is 2-methoxyethanol (2-ME). The objective of this study was to evaluate the effect of Mucuna pruriens (MP) seed fraction on spermatogenesis, including number of spermatogenic cells and spermatozoal membrane protein profiles after exposure to 2-ME in mice. Methods This study was of experimental design. Thirty mice were randomized into 5 groups, i.e. 2 control groups and 3 treatment groups. All mice were injected subcutaneously with 2-ME doses of 100mg/kg body weight (BW)/day, for a period of 12 days. Positive (PC) and negative controls (NC) were treated with carboxy methyl cellulose (CMC). The three treatment groups were given MP seed fraction in doses of 14 (T1), 28 (T2) and 56 mg/kg BW (T3), respectively, from day 13 until day 64. Data on spermatogenic cells were collected from histological cross-sections and analyzed with one-way ANOVA. The spermatozoal membrane protein profile was identified by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) with silver staining and were analyzed descriptively. Results Administration of MP seed fractions resulted in significantly different numbers of spermatocytes I and round spermatids between PC and T1, T2, and T3. A protein with the molecular weight of 41.6 kDa was expressed in all groups except the positive controls, while a 24.5 kDa protein was expressed in the positive controls only. Conclusion MP seed fraction effectively recovers spermatogenesis loss in mice due to 2-ME exposure.